Perencanaan Tempat Pengolahan Sampah Reduce, Reuse, Recycle (TPS 3R): (Studi kasus di Desa Lora, Kecamatan Mataoleo, Kabupaten Bombana, Sulawesi Tenggara) - Tahmid, Tahmid; Ndibale, Wa; Pratiwi, Yunita Eka (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2025)
Covers an area of approximately 23.05 km² with a population of 1,738 people in 2024. This study aims to identify the generation and composition of waste in Lora Village, as well as to determine the projected waste generation for the next ten years and the design of a TPS 3R (Reduce, Reuse, Recycle Waste Processing Site) that is suitable for the local conditions. The research method employs both quantitative and qualitative descriptive approaches through field surveys, interviews, and waste generation measurements. Data analysis was conducted to determine the amount and composition of organic and inorganic waste, as well as population projections using the geometric method. The research results show that the total waste weight is 0.094 kg/person/day with a volume of 3.333 liters/person/day. The waste composition consists of 85.11% organic and 14.89% inorganic materials. The projected waste generation for the next ten years reaches 78,880 kg/year with a volume of 2,796,900 liters/year. The designed TPS 3R includes a composting area (45 m²), sorting area (15 m²), packaging area (22 m²), inorganic storage area (20 m²), residue area (35 m²), and green open space (60 m²). The total land area required is 251 m².